Catechins: Protective mechanism of antioxidant stress in atherosclerosis - Sheng, Yuhan; Sun, Yizhuo; Tang, Yang; Yu, Yanru; Wang, Jiarou; Zheng, Fengjie; Li, Yuhang; Sun, Yan (Frontiers in Pharmacology, 2023)
In recent years, more and more attention has been paid to the health benefits of tea, particularly its potential in the prevention and treatment of atherosclerosis (AS). Oxidative stress and abnormal lipid metabolism are major factors that contributes to the development of AS. Tea, which originates from China, is believed to help prevent AS. Research has shown that tea is rich in catechins, which is considered as a potential source of natural antioxidants. Catechins is the most abundant form of antioxidant present in green tea, and is believed to be the main compound responsible for the antioxidant activity of tea. The antioxidant properties of catechins are largely dependent on their chemical structure and the number of hydroxyl groups present. As an exogenous antioxidant, catechins can effectively eliminate lipid peroxidation products. They can also play an antioxidant role indirectly by activating the endogenous antioxidant system through regulating enzyme activity and signal pathways. In this review, we summarized the preventive effect of catechin in AS, and emphasized that improving antioxidant effect and lipid metabolism disorders of catechins is key to managing AS.